1987
DOI: 10.1037/0022-3514.53.4.693
|View full text |Cite
|
Sign up to set email alerts
|

"Eating lightly" and the self-presentation of femininity.

Abstract: In Experiment 1, male and female subjects were given an opportunity to snack as they participated in a "get-acquainted study" with a same-sex or opposite-sex partner (confederate) whose social desirability was manipulated. Consistent with the hypothesis that women may eat less when motivated to present themselves in a feminine light, female subjects ate significantly less with a desirable male partner than in the remaining three conditions. In contrast, male subjects did not eat more (or less) with a desirable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
132
0
4

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(141 citation statements)
references
References 37 publications
(51 reference statements)
5
132
0
4
Order By: Relevance
“…This may be a result of impression management and the desire to be seen in a positive light in front of strangers (Leary & Kowalski, 1990;Tice et al, 1995). Mori, Chaiken & Pliner (1987), however, argued that impression management is just as likely to take place between familiar companions of the opposite sex, especially if they find each other desirable. SimilarIy, Wansink and Park (2000) reported that whereas women decrease their food intake as an attempt to appear more feminine, men consider overeating to be a sign of masculinity and power.…”
mentioning
confidence: 99%
“…This may be a result of impression management and the desire to be seen in a positive light in front of strangers (Leary & Kowalski, 1990;Tice et al, 1995). Mori, Chaiken & Pliner (1987), however, argued that impression management is just as likely to take place between familiar companions of the opposite sex, especially if they find each other desirable. SimilarIy, Wansink and Park (2000) reported that whereas women decrease their food intake as an attempt to appear more feminine, men consider overeating to be a sign of masculinity and power.…”
mentioning
confidence: 99%
“…Despite increasing research addressing the etiology of these problems, it remains unclear what psychological characteristics represent precursors of pathological eating behavior (American Psychiatric Association, 1987). Nonetheless, a sizable literature implicates sociocultural (e.g., Boskind-Lodahl, 1976;Rodin, Silberstein, & Striegel-Moore, 1985), social cognitive (e.g., Mori, Chaiken, & Pliner, 1987;Polivy, Herman, Jazwinski, & Olmsted, 1984), and psychodynamic (e.g., Bruch, 1973Bruch, , 1982 factors as precursors of eating-related problems.Researchers and clinicians have implicated the self-concept in vulnerability to appearance-related and eating-related difficulties (Cash & Green, 1986;Markus, Hamill, & Sentis, 1987). Self-concept deficiencies may contribute significantly to the development of the negative self-evaluation, misperceptions of internal emotional and somatic states, and disturbed eating patterns characteristic of these syndromes (Mori et al, 1987).…”
mentioning
confidence: 99%
“…Nonetheless, a sizable literature implicates sociocultural (e.g., Boskind-Lodahl, 1976;Rodin, Silberstein, & Striegel-Moore, 1985), social cognitive (e.g., Mori, Chaiken, & Pliner, 1987;Polivy, Herman, Jazwinski, & Olmsted, 1984), and psychodynamic (e.g., Bruch, 1973Bruch, , 1982 factors as precursors of eating-related problems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the presence of a noneating observer leads to suppression of food intake (Herman, Polivy, & Roth, 2003). Studies on impression management with eating companions also show that unfamiliarity (Tice, Butler, Muraven, & Stillwell, 1995), opposite gender, attractiveness (Mori, Chaiken, & Pliner, 1987), and the weight of the co-actors (de Luca & Spigelman, 1979) increase the suppression of food intake even further, because these factors increase impression motivation (Leary & Kowalski, 1990), that is, the desire to present the self favorably.…”
Section: Social Influence On Food Consumptionmentioning
confidence: 99%